Antagonistic Effect of the Lactic Bacteria Isolated from the Camel Milk on Staphylococcus aureus in Yoghourt Manufacturing - Belkis; Arezki Bitam (Journal of Pharmacy and Nutrition Sciences, 2013)
This paper deals with the lactic bacteria found in the raw camel milk producing antibacterial substances. Samples of milk were obtained from female camels of herds from nomads living in the south of Algeria. The antibacterial activity of the bacteria was tested on Staphylococcus aureus strains and to highlight this activity in a yoghourt for therapeutic purpose. Among the seven (07) strains of lactic bacteria which were isolated from camel milk Lb. fermentum (Lc17) presented the highest antagonistic effect on S. aureus. After incorporation in the yoghourt ,It was verified that there was no interaction between the lactic ferments of yoghourt and Lb. fermentum and no modification of the acidity. However the realization of a yoghourt containing Lb. fermentum with shown a total inhibition of Staphylococcus aureus to a load 5,87 log UFC compared to that of yoghourt made up exclusively of lactic leavens, after 4 hours of incubation in mixed culture.